2020
DOI: 10.1186/s12967-020-02458-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of initial treatment and prognostic factors on postprogression survival in BRAF-mutated metastatic melanoma treated with dacarbazine or vemurafenib ± cobimetinib: a pooled analysis of four clinical trials

Abstract: Background We sought to identify patient subgroups with distinct postprogression overall survival (ppOS) outcomes and investigate the impact of original treatment assignment and initial postprogression treatment (ppRx) on ppOS. Methods Recursive partitioning analysis (RPA) was performed to model relationships between prespecified covariates and ppOS in patients with BRAFV600-mutated metastatic melanoma who had experienced progressive disease (PD) following treatment with cobimetinib plus vemurafenib, vemuraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Similar proportions of patients across these studies received subsequent anticancer treatment with immunotherapy or further targeted therapy. Although the extent to which long-term OS is influenced by subsequent treatment is unclear, recent analyses suggest that patients who progress following treatment with BRAF and/or MEK inhibitors derive an OS benefit from subsequent treatment with immunotherapy or additional targeted therapy (12). Identification of subgroups of patients likely to achieve long-term treatment benefit is important to inform treatment decisions in the management of patients with metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar proportions of patients across these studies received subsequent anticancer treatment with immunotherapy or further targeted therapy. Although the extent to which long-term OS is influenced by subsequent treatment is unclear, recent analyses suggest that patients who progress following treatment with BRAF and/or MEK inhibitors derive an OS benefit from subsequent treatment with immunotherapy or additional targeted therapy (12). Identification of subgroups of patients likely to achieve long-term treatment benefit is important to inform treatment decisions in the management of patients with metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration is that our analysis simplified our treatment variations by categorising them into major groups. We did not distinguish different types of immunotherapies or targeted therapies, either in monotherapies or combination therapies as well as with or without surgical metastasectomy or radiotherapy, nor evaluated the sequence of different treatments given, which past studies had reported variations in survival outcomes 42–48 . Furthermore, while we excluded ocular melanoma, which is highly resistant to systemic therapies and typically treated differently, we did not further analyse the differences in prognosis among other melanoma subtypes due to our limited sample size and data regarding the primary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that BRAF/MEKi therapy might also affect the tumor microenvironment (TME) and improve durable tumor surveillance, thus having a long-term beneficial effect. It has been shown that these long-term effects are most likely in patients with CR to TT [ 30 ]. In particular, it has been suggested by Long and colleagues, that patients with a CR and favorable baseline characteristics, such as a lower initial tumor burden, fewer metastatic tumor sites, or normal LDH-levels, may be more likely to show a stronger and more sustained response, thus driving long-term survival [ 19 ].…”
Section: Discussionmentioning
confidence: 99%